Prognostic significance of aminopeptidase‐N (CD13) in hepatoblastoma. Issue 4 (14th July 2015) - Saida, Satoshi; Watanabe, Ken‐ichiro; Kato, Itaru; Fujino, Hisanori; Umeda, Katsutsugu; Okamoto, Shinya; Uemoto, Shinji; Hishiki, Tomoro; Yoshida, Hideo; Tanaka, Shiro; Adachi, Souichi; Niwa, Akira; et al.
Abstract Background Hepatoblastoma is a rare childhood malignant tumor that originates from immature hepatic cells. Aminopeptidase‐N(CD13), an ectopeptidase that promotes tumor invasion and metastasis, is expressed in fetal stage hepatic progenitor cells, although its role in hepatoblastoma remains unclear. Methods The expression pattern of CD13 was investigated on immunohistochemistry in 30 tissue samples from 27 hepatoblastoma patients (16 with predominantly embryonal [pE] histology and 14 with predominantly fetal [pF] histology). Immunoreactive score (IRS) was used to quantify staining data, and the relationship between CD13 expression, clinicopathological factors, and clinical outcome was investigated. The biological function of CD13 was also examined in the hepatoblastoma cell lines Huh6 and HepG2. Results All specimens stained positive for CD13, with higher CD13 expression in pE than in pF hepatoblastoma samples (median IRS, 4; range, 2–9 vs 2; range, 1–4). Strong CD13 expression was correlated with vascular invasion. Five year event‐free survival and overall survival were better in patients with CD13low than in those with CD13high tumors (100% vs 51.0%, P = 0.026; and 100% vs 74.0%, P = 0.114, respectively). A CD13‐neutralizing antibody and the potent CD13 inhibitor, Ubenimex, suppressed invasive activity in HepG2 cells in vitro. Conclusions CD13 expression is associated with hepatoblastoma invasiveness and could be a novel prognostic marker for hepatoblastoma.